PERLINDUNGAN HUKUM TERHADAP PEREMPUAN KORBAN TINDAK PIDANA PERDAGANGAN ORANG DI KOTA PEKANBARU - Sari, Intan Permata; Firdaus, Emilda; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Protection is defined as protection provided by legislation regulated by this law, starting from someone who can be identified as a victim of trafficking in persons, the process of investigation, prosecution and social rehabilitation to the process of returning victims of trafficking in persons. Giving protection to victims by the police to provide security from the threats posed by perpetrators by the police still raises concerns that the police will act arbitrarily in conducting investigations, where the police agency in investigating this case is trying to protect the perpetrators of crime. Because in the case of trafficking women often blame the victims in a case. While the police still have a feeling of not sympathizing with the victims, this closes the possibility that there will be a neglect of the victims to get their rights they should get. Not infrequently, sometimes cases of criminal acts of trafficking go to court institutions, this is because the police cannot continue the case due to a lack of evidence. Even though the victim's information has been able to strengthen the evidence that the criminal act of trafficking occurred. In the protection given to victims of criminal acts of trafficking in people in Pekanbaru, there is still no concern. The connection is that victims are left to leave without getting the protection provided by the authorities, this is also due to the low education of the victims so that these victims do not know what rights they must receive. Whereas in the regulations governing the crime of trafficking in persons it has been explained. The police should provide protection by implementing and implementing women victims of trafficking in crime to protect victims from threats that will befall them, from investigations to after stages in the judiciary. In the future, the application of the law to the provision of assistance to victims of crime is not only limited to the legislation, but in its implementation it must also be realized for the sake of justice that must be upheld.Keywords: Protection - Police - Crime of Trafficking in Persons